Psychometric Evaluation of the Persian PSSUQ Third Edition and Usability Assessment of a Library Website - Kowsar Eftekhari; Elahe Amouzadeh; Roya Nikbakht; Siavash Etemadinezhad (بهداشت و ایمنی کار)
Introduction: Computer-based systems have become integral to every aspect of daily life, with the successful performance of such systems heavily reliant on error-free software. Given the significance of these systems, tools are essential for evaluating their usability. One such tool is the Post-Study System Usability Questionnaire (PSSUQ). The present study aimed to localize and psychometrically evaluate the Persian version of the third edition of the PSSUQ and assess the usability of the library website at Mazandaran University of Medical Sciences. Material and Methods: This descriptive cross-sectional study employed the Backward-Forward method for translating the questionnaire. The study population included 314 participants for cultural adaptation of the scale and 147 postgraduate students for evaluating the library website, all from Mazandaran University of Medical Sciences. Content validity was assessed using the Content Validity Index (CVI) and Content Validity Ratio (CVR). Reliability was determined via Cronbach’s alpha, and exploratory factor analysis was performed. Data analysis was conducted using SPSS version 16, adhering to ethical guidelines at all stages of the study. Results: The overall content validity index (CVI) of the questionnaire was 0.96, while the overall content validity ratio (CVR) was satisfactory, with clarity and simplicity both scoring 0.91 and necessity at 0.75. Cronbach’s alpha coefficient was 0.95, with correlations between items exceeding 0.30. No significant differences in the usability of the library website were observed based on age, gender, field of study, educational level, or year of admission. Conclusion: The Persian version of the third edition of the PSSUQ is a valid and reliable tool for evaluating system usability and user satisfaction with digital systems. It holds substantial potential for identifying system weaknesses and areas requiring improvement.